A patient's guide to surgery - Bradley, Edward L. (University of Pennsylvania Press, 1994)
In a Patient's Guide to Surgery, Dr. Edward L. Bradley III explains all you need to know to prepare yourself for the surgical experience. This book describes how you can actively participate in the decision-making process and, as a result, improve your chances for successful surgery and recovery. A Patient's Guide to Surgery also lists specific questions you should consider when evaluating a doctor, a hospital, or a prepaid health plan.